ScenarIoT: Support for Scenario Specification of Internet of Things-based Software Systems - da Silva, Valéria Martins; Travassos, Guilherme H. (Anais Estendidos do Congresso Brasileiro de Software: Teoria e Prática (CBSoft); 2020: Anais Estendidos do XI Congresso Brasileiro de Software: Teoria e PráticaDO - 10.5753/cbsoft_estendido.2020.14628, 2020)
As well as any paradigm shift, the Internet of Things (IoT) brings up challenges related to several areas of research, including Software Engineering at different stages of development. This work proposes the ScenarIoT approach aiming to support the specification of scenarios when developing software systems on the IoT background. This approach is grounded on Interaction Arrangements - designed by applying an evidence-based approach – which represents recurrent flows of interaction between abstract elements of the IoT domain. These results presented can contribute to the progress of research on IoT from the lens of the Software Engineering research field.